Impact Of Source Credibility Dimensions On Consumers Purchase Intention: An Empirical Study On Textile Industry - Reddy, Dr. M Siva Koti; Lakshmi, Ms. G.Tejo (The journal of contemporary issues in business and government, 2021)
The textile and equipment industry of the country India accounts almost about 4% of the global textile market. This sector is one of the expanding and most crucial sectors of the economy in the aspects of production, income by exchange rate and job opportunities. The objective of the study is to understand the theoretical concepts of credibility of the message source and its components. Our objective is to study the impact of message trustworthiness, expertness and attractiveness on consumer purchase intention. It is assumed that the true marketing concept professional must discover what consumers want or need and try to meet those needs if it makes economic and strategic sense. A marketing message is a means of communication designed to influence customers. The questionnaire consists of nine questions and all the questions were made in relevance to likert scale which is very famous in capturing intention and behavioral studies. The items in the scale are validated using explorative factor analysis. The associations between the study constructs are analyzed by regression analysis and discussions are made on the results obtained.